PENGEMBANGAN INSTRUMEN PENGETAHUAN DAN SIKAP IBU DALAM MELAKUKAN PERAWATAN NEONATUS BERBASIS PEMODELAN RASCH - Sinaga, Nelly Dameria; Rahma Dewi Agustini (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKes Banyuwangi, 2023)
Late sepsis in babies aged 7 days or more is caused by a lack of cleanliness in newborn care by the mother. Maternal knowledge regarding neonatal care skills still needs to be considered. This research uses an instrument that must be tested for validity and reliability based on Rasch modeling so that it can be seen which question numbers are too difficult and too easy to answer so that the instrument can be accepted in research. Validity and reliability tests can use the Rasch modeling application formula (Rasch model). The aim of this research is to validate and reliability research instruments regarding mothers' knowledge and attitudes in carrying out neonatal care. The design in this research uses quantitative analysis by adopting 3 research journals. This questionnaire was tested on 30 pregnant women at the Independent Practice of Midwife Ana Mariana. The research results showed that the questionnaire was valid and reliable, meaning it was said to be suitable for use by the general public. The results of the validity test value for row variance explained by size and raw unexplained variance (total) for knowledge and attitudes are between 40-60% with Good criteria. Meanwhile, the reliability test uses item reliability and Cronbach alpha in the good category. The results found that the questionnaire was valid and reliable, meaning it could be used as a research instrument in subsequent research.